2016
DOI: 10.1590/1678-775720150203
|View full text |Cite
|
Sign up to set email alerts
|

The presence of Helicobacter pylori in oral cavities of patients with leukoplakia and oral lichen planus

Abstract: Objective Helicobacter pylori infection is one of the most common bacterial infections in men. This gastrointestinal pathogen is closely related to gastritis, peptic ulcers, and the increased risk of gastric cancer. Numerous studies have indicated oral cavities as possible Helicobacter pylori reservoirs. Helicobacter pylori has been detected both in supragingival and subgingival plaques, and also in saliva. In addition, the relationship between lesions of oral mucosa and the presence of H. pylori has been eval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(43 citation statements)
references
References 23 publications
(29 reference statements)
1
35
0
Order By: Relevance
“…Helicobacter pylori is one of the most susceptible infection factors of OLP. Both positive and negative relations between H. pylori infection and OLP occurrence have been reported by different detection methods (Attia et al , ; Pourshahidi et al , ; Kazanowska‐Dygdala et al , ). In our research, g. Helicobacter , the genus which H. pylori belongs to, showed low abundance both in OLP and BC group and no significant difference can be detected.…”
Section: Discussionmentioning
confidence: 99%
“…Helicobacter pylori is one of the most susceptible infection factors of OLP. Both positive and negative relations between H. pylori infection and OLP occurrence have been reported by different detection methods (Attia et al , ; Pourshahidi et al , ; Kazanowska‐Dygdala et al , ). In our research, g. Helicobacter , the genus which H. pylori belongs to, showed low abundance both in OLP and BC group and no significant difference can be detected.…”
Section: Discussionmentioning
confidence: 99%
“…The potential of these microorganisms to promote inflammatory conditions in the oral environment was proposed on this basis. 34 There is also a relationship between the presence of pathological gingival pockets and H. pylori infections. Umeda et al found that in patients with gastric H. pylori infection, the detection frequency of these bacteria in the oral cavity was 4-fold higher (41.2%) when patients had gingiva with a pocket depth of ≥4 mm than those with healthy periodontium (9.1%).…”
Section: Epidemiology Of Oral H Pylori Infectionsmentioning
confidence: 99%
“…The role of torque teno virus (TTV) [9,10], Epstein-Barr virus (EBV) [11] and Candida albicans [8,[12][13][14][15][16] in leukoplakia development and carcinogenesis remains to be clarified, too. Additionally, it has been also demonstrated that specific bacterial infections like Helicobacter pylori [17] or the intracellular Mycoplasma salivarium [18] could also be involved in this process.…”
Section: Introductionmentioning
confidence: 99%